Effect of level of supplemental alfalfa and its method of processing on intake and utilization of wheat straw - B.A. Lintzenich; R.C. Cochran; E.S. Vanzant; J.L. Beaty; G. St. Jean; Robert T. Brandt; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1993)
Sixteen ruminally fistulated steers were used to study the effects of supplemental alfalfa level (.25 or 1.0% body weight [BW]) and method of processing (hay or pellets) on wheat straw utilization. Response to increased level of supplemental alfalfa did not dependent on method of processing (longstem vs pelleted) for the quality of alfalfa (22.7% CP) used in this trial. Increasing the level of alfalfa from .25 to 1.0% of BW reduced (P#.02) straw intake and diet digestibility, but increased (P<.002) digestible dry matter intake by steers. With high quality hay, ground and pelleted alfalfa elicits the same type of response as longstem alfalfa.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Supplements; Alfalfa; Processing; Cattle; Wheat straw